(Volvariella volvaceae) (Analysis of equilibrium moisture content and drying constant of mushroom (Volvariella volvaceae)) - Rizal Alamsyah; Putiati Mahdar; Ishak Syah (Balai Besar Industri Agro, 1995)
In order to obtain the better mushroom drying operation, it requires proper information of its equilibrium moisture content (Me) and drying constant since it was very useful for storag.The objective of this research was to design Me and K models.The models were function of drying temperature and designed based on infinite slab and sphere geometry.The experiments were conducted at 35,40,45,and 50 degree C,on blanched/unblanched condition and were operated at drying air velocity of 1.0 1.5 2.0, and 2.5 m/s.The Me and K models based on infinite slab gave better results.